Enamine‐Based Cross‐Linkable Hole‐Transporting Materials for Perovskite Solar Cells. Issue 1 (18th November 2020) - Vaitukaitytė, Deimantė; Al-Ashouri, Amran; Daškevičienė, Marytė; Kamarauskas, Egidijus; Nekrasovas, Jonas; Jankauskas, Vygintas; Magomedov, Artiom; Albrecht, Steve; Getautis, Vytautas
Abstract : The development of the simple synthesis schemes of organic semiconductors can have an important contribution to the advancement of related technologies. In particular, one of the fields where the high price of the hole‐transporting materials may become an obstacle toward successful commercialization is perovskite solar cells. Herein, enamine‐based materials that are capable of undergoing cross‐linking due to the presence of two vinyl groups are synthesized. It is shown that new compounds can be thermally polymerized, making the films resistant to organic solvents. This can allow the use of a wet‐coating process for the deposition of the perovskite absorber film, without the need for orthogonal solvents. Cross‐linked films are used in perovskite solar cells, and, upon optimization of the film thickness, the highest power conversion efficiency of 18.1% is demonstrated. Abstract : Thermal cross‐linking of new enamine‐based hole‐transporting materials is shown to provide an advantage in p–i–n perovskite solar cells. Due to the improved resistance to organic solvents, the cross‐linked films manage to withstand solution processing of the perovskite absorber layer. This leads to an improved open‐circuit voltage and over 18% efficiency for the devices with the V1187 material.